If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 + 7x + -9 = 82 Reorder the terms: 3 + -9 + x + 7x = 82 Combine like terms: 3 + -9 = -6 -6 + x + 7x = 82 Combine like terms: x + 7x = 8x -6 + 8x = 82 Solving -6 + 8x = 82 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 8x = 82 + 6 Combine like terms: -6 + 6 = 0 0 + 8x = 82 + 6 8x = 82 + 6 Combine like terms: 82 + 6 = 88 8x = 88 Divide each side by '8'. x = 11 Simplifying x = 11
| 5(y+-7)+-2y=1+-3[(4y+7)+-2(y+-3)] | | 10r-r= | | 5x^2+26x+32=0 | | 3(4x-2y)+2(x+2y)= | | 2x+11=6x-5-4x | | 11x-3=2x+9 | | 4x/3+2=5 | | -35x+12=28x+19 | | 2x^2+3((-2x+13)/3)^2-35=0 | | A+B+B+B+80+9=100 | | 4=ln(y+4) | | 4x+28x-32=0 | | 4(x-6)-6=x-14 | | 6*3/7*3*1/3/1*2/7 | | 4=Ln(y+1) | | 11/5n=4n+20 | | 6x+8=6x-13 | | -13.00+2.00x= | | ProveA+B+B+B+80+90=100 | | 0.1x+(3x+20)/5=0.5 | | (3x-2y+1)dx+(3x-2y+3)dy=0 | | 4(x-6)-6=4x-14 | | y(4x+y)dx-2(x^2-y)dy=0 | | 3(x+6)-4=6x-2 | | 8p-7p+3=-8 | | 66666666d=4 | | 15/14/2/23 | | 7x+4y=33 | | -5a-3=-7(7+4a) | | 7-(3*x)=38 | | 7/2-x=18/2 | | 3-(12+2x)=1 |